ANALlSA KECEPATAN PUTARAN TABUNG BALL MlLLlNG TERHADAP SUSEPTlBILlTAS MAGNETlK DAN KOMPOSlSl SERTA UKURAN PARTlKEL OKSlDA BESl PASlR ALAM SUNGAl ROKAN - Tasyha Dwi Safira; Salomo Sinuraya; Erwin Amiruddin; Rahmondia Nanda Setiadi (Universitas Riau, 2023)
Magnetic susceptibility and composition of magnetic particles from the natural sand iron oxide, at Rokan River in Riau Province as a function of the rotating speed of ball milling tubes. Samples are separated the magnetic particles from non-magnetic particles using iron sand separator (ISS), called the ISS product. Refinement using neodymium iron boron magnet (NdFeB). The ball milling process is carried out for 80 hours using combined iron balls with diameter of 0.7 cm (48 balls), 1.5 cm (24 balls), and 2 cm (16 balls) with variety milling tube rotational speeds of 100, 150, and 200 rpm. The calculation of the magnetic susceptibility value is carried out based on the values of B0 and BT, while the composition of the sample by X-ray fluorescence (XRF) and the magnetic particle size of the sample is classified by scanning electron microscope. The result of the study indicates that the magnetic susceptibility of the ISS product has a value 2,895.99 × 10-5, while the value of the magnetic susceptibility of ball milling product increases with the increase in the rotating speed of the tube, namely 27,997.52 × 10-5, 29,975.27 × 10-5, and 30,690.44 × 10-5. XRF results show that the magnetic element Fe increased from 32.069% to 39.645%, while the non-magnetic element Si decreased from 31.127% to 29.187%. The average particle size obtained was smaller as the rotational speed of the milling tube increased, namely 679.72 nm, 619.14 nm, and 568.94 nm.